Isolated Nocardiosis, an Unrecognized Primary Immunodeficiency? - Martínez-Barricarte, Rubén (Frontiers in Immunology, 2020)
Nocardiosis is an infectious disease caused by the Gram-positive bacterium Nocardia spp. Although it is commonly accepted that exposure to Nocardia is almost universal, only a small fraction of exposed individuals develop the disease, while the vast majority remain healthy. Nocardiosis has been described as an “opportunistic” disease of immunocompromised patients, suggesting that exposure to the pathogen is necessary, but a host predisposition is also required. Interestingly, increasing numbers of nocardiosis cases in individuals without any detected risk factors, i.e., without overt immunodeficiency, are being reported. Furthermore, a growing number of evidence have shown that selective susceptibility to a given pathogen can be caused by primary immunodeficiency (PID). This raises the question of whether an undiagnosed PID may cause nocardiosis affecting otherwise healthy individuals. This review summarizes the specific clinical and microbiological characteristics of patients with isolated nocardiosis published during the past 30 years. Furthermore, it gives an overview of the known human immune mechanisms to fend off Nocardiosis spp. obtained from the study of PIDs and patients under immunomodulatory therapies.